Realization of Rolling Bearing Serialization based on CREO Platform - Qiu Haifei (Jixie chuandong)
For improving interchangeability of bearing product,the method of rolling bearing serializing design is researched under the environment of CREO. The parametric CAD model template of deep groove ball bearing 6208 is designed,and then the structural parameters edited of different specifications bearing and its model reconstruction are achieved on this basis. The data exchange and operation mode of the rolling bearing is established with DLL technology which used C + + language as development tool,and the interactive interface of the rolling bearing serialization design based on the CREO platform is successfully developed. Because of that,not only effectively enhance the flexibility of bearing product development,but also provides a technical basis for similar product serialization design and market transformation.